Pengabdian pada Santri Pondok Pesantren Darul Huffaz tentang Kebersihan Toilet dan Cuci Tangan Pakai Sabun - Wayan Aryawati; Angeli Natasha. HS; Desy Adelia; Fitri Oktavianasari; Mega Alamzarwati; Meisya Rahma Syifa; Reni Rianti; Siti Nur Aziza; Veronika Ardana; Wita Dinarti; Renita Saputri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Toilet is a crucial sanitation facility for the disposal of human waste and handwashing, playing a pivotal role in maintaining the cleanliness and health of individuals and communities. Handwashing with Soap (HWS) is a vital practice for cleaning hands from dirt, serving to prevent the spread of disease-causing germs, including diarrhea, helminthiasis, and Acute Respiratory Infections (ARIs). This devotion aims to understand the health history through the practice of HWS at Darul Huffaz Islamic Boarding School in Pesawaran Regency. The research method employs SWOT Analysis as a practical tool to identify strengths, weaknesses, opportunities, and threats related to the existing issues. Community Service Activities (CSA) are carried out through the dissemination of information on toilet hygiene and HWS, as well as the production of natural ingredient-based handwashing soap, particularly using Aloe vera. The results of the CSA activities indicate that the dissemina-tion and demonstration of toilet hygiene and HWS are effective, with participants motivated to maintain toilet cleanliness and adopt a healthy and hygienic lifestyle (PHBS). The conclusion reveals that these activities provide positive benefits for students and the boarding school's management. Through training methods, interactive discussions, demonstrations, and practical soap-making sessions, participants can acquire valuable knowledge and skills. This activity involves 50 participants and takes place in the girls' prayer room at Darul Huffaz Islamic Boarding School.